PENGEMBANGAN BAHAN AJAR BERBASIS PMRI PADA MATERI SEGITIGA KD.6.1 UNTUK SISWA SMP KELAS VII - Wahyuni, Dedek; Lusiana, Lusiana; Marhamah, Marhamah (Jurnal Dosen Universitas PGRI Palembang)
Abstract: This study aims to produce a valid triangle LKS material and practical-based PMRI. This type of research is a research & development (development research). The development model used was adapted from the model of development according to Sugiyono consisting of seven stages. These stages include: the potential and problems, data collection, product design, design validation, design revisions, test products, the revision of the product (the final product). Due to the limitations of time, effort, and cost, then the final result in the form LKS valid and practical learning with stage revisions have been done twice. LKS learning has been validated by two professors of mathematics education and one teacher of mathematics. The tests showed an average 89% and enter into valid criteria. LKS then tested is limited and student questionnaire responses obtained with an average score of 80%, so that the students response to LKS learning practical and easy to use by students. From the results of this study concluded that the LKS developed a valid and practical, so that teaching materials based on the material PMRI triangle KD.6.1 for junior high school students of class VII is ready to be tested to a large scale to see the potential effects of its use.Â Keywords: development, instructional materials, triangle, PMRI